2021
DOI: 10.3390/microorganisms9040682
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Bacteria as an Emerging Tool to Manage Bacterial Rice Pathogens

Abstract: As a major food crop, rice (Oryza sativa) is produced and consumed by nearly 90% of the population in Asia with less than 9% produced outside Asia. Hence, reports on large scale grain losses were alarming and resulted in a heightened awareness on the importance of rice plants’ health and increased interest against phytopathogens in rice. To serve this interest, this review will provide a summary on bacterial rice pathogens, which can potentially be controlled by plant growth-promoting bacteria (PGPB). Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 191 publications
1
44
0
1
Order By: Relevance
“…Many of them have been considered as vital drivers in bio-geological processes [2]. Certain microbes are found to be beneficial in a variety of ways, such as enhancing plant production [3] or controlling pathogens [4]. However, they also possess some adverse effects, such as causing plant diseases [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Many of them have been considered as vital drivers in bio-geological processes [2]. Certain microbes are found to be beneficial in a variety of ways, such as enhancing plant production [3] or controlling pathogens [4]. However, they also possess some adverse effects, such as causing plant diseases [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…An assortment of abiotic and biotic elements shape soil-and plant-related living spaces and adjust the creations and exercises of their microbial networks, which thus bear upon the nature of their development of plants and the creation of root exudates ( Jain et al, 2020 ). Bacteria harbor in roots, depending on the incredible variety of natural root exudates, which in the long run influences the growth and development of the plant ( Ngalimat et al, 2021 ). Here, in this study, we examined the impact of rice rhizosphere regulated with local bacterial consortia developed to increase the uptake the N/P/K as nutrients from the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotics produced by these bacteria have an inhibitory or killing effect on phytopathogens. In addition, it has been found that some of these compounds also have antiviral, anticancer, antioxidant, and cytotoxic properties [90,108]. The antibiotics produced by Bacillus include bacilysin, chlortetain, subtilin, bacillaene, or surfactin.…”
Section: Mechanisms Of Reduction Of the Impact Of Xenobiotic-induced Stress Conditions By Bacterial Endophytesmentioning
confidence: 99%
“…The antibiotics produced by Bacillus include bacilysin, chlortetain, subtilin, bacillaene, or surfactin. Strains representing the genus Pseudomonas were found to have the ability to synthesize 2,4diacetyl phloroglucinol (DAPG), pseudomonic acid, phenazine-1-carboxylic acid (PCA), pyoluteorin, pyrrolnitrin, or oomycin A [90,108].…”
Section: Mechanisms Of Reduction Of the Impact Of Xenobiotic-induced Stress Conditions By Bacterial Endophytesmentioning
confidence: 99%
See 1 more Smart Citation